Personal Branding Influencer Annisa Asyabilla Melalui Instagram - Ramadani, Fadillah; Widhihatmini, Widhihatmini (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2025)
Today's life is inevitable from technological advancements. Instagram is one of the platforms used bytoday's society as a favorite means of individuals to publish activities, goods, places or themselves inthe form of photos, videos, and images. The rise of Instagram as a personal branding tool compared tointeracting with others makes it a new phenomenon. Everyone competes to build personal brandingaccording to their fields of expertise and interests, including individuals who are referred to asinfluencers. The purpose of this study is to find out the personal branding of Influencer Annisa Asyabilathrough Instagram. This study uses 11 theoretical aspects of Rampersad. This study uses a qualitativeapproach. The data collection method uses observations. interviews, and documentation. Data analysistechniques include data reduction, data presentation, and conclusion drawn. The results of the studyshow that Annisa Asyabilla has personal branding, namely the authenticity of OOTD content by havinga posture with drees and baggy jeans, integrity through natural and honest content, consistency infashion mix and match content, specialization in fashion and drawing, authority created fromconfidence, and visible privileges from her personalitymultitalented, cheerful and socially aware,relevant to his followers who like mix and match outfits, visibility through endorsements from hispersonal branding, persistence seen from his efforts to become an influencer and achieve his desires,kindness reflected in his interaction with followers and productivity, and performance from his focus onsharing positive things as an influencer. The conclusion of this study is that influencer Annisa Asyabillahas fulfilled the aspects of personal branding on Instagram which include: authenticity, integrity,consistency, specialization, authority, uniqueness, relevance, visibility, persistence, kindness, andperformance.